2018
DOI: 10.1089/ten.tea.2018.0053
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Progenitor-Laden Bridges Support Earlier Axon Regeneration Following Spinal Cord Injury

Abstract: Spinal cord injury (SCI) results in loss of tissue innervation below the injury. Spinal progenitors have a greater ability to repair the damage and can be injected into the injury, but their regenerative potential is hampered by their poor survival after transplantation. Biomaterials can create a cell delivery platform and generate a more hospitable microenvironment for the progenitors within the injury. In this work, polymeric bridges are used to deliver embryonic spinal progenitors to the injury, resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 84 publications
(191 reference statements)
0
33
0
Order By: Relevance
“…Mice receiving the hydrogel tubes and bridges also recovered greater locomotor function compared to the controls, that corroborate the histological findings. Interestingly, the increased axon density at 8 weeks in the 5-tube composites (1744 axons/mm 2 ) is an improvement over that observed in PLG bridges (740 axons/mm 2 ) implanted into a mouse hemisection model [36,37], which may be due to the more closely matched mechanical properties of the hydrogel to the nervous tissue (1-300 kPa [63][64][65]). Vascular tissue and muscle require high tensile strength, and there are a number of modifications to the material that can be made to properly match these tissues.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Mice receiving the hydrogel tubes and bridges also recovered greater locomotor function compared to the controls, that corroborate the histological findings. Interestingly, the increased axon density at 8 weeks in the 5-tube composites (1744 axons/mm 2 ) is an improvement over that observed in PLG bridges (740 axons/mm 2 ) implanted into a mouse hemisection model [36,37], which may be due to the more closely matched mechanical properties of the hydrogel to the nervous tissue (1-300 kPa [63][64][65]). Vascular tissue and muscle require high tensile strength, and there are a number of modifications to the material that can be made to properly match these tissues.…”
Section: Discussionmentioning
confidence: 88%
“…For example, the spinal cord is a highly organized structure with predominantly rostral-caudal alignment of axons and myelin, making it an ideal tissue for evaluating aligned biomaterial bridges. Previous work using multi-channel bridges has shown robust directed axon elongation [9,[36][37][38][39][40]. An additional design feature of these bridges is their high degree of porosity [37], allowing for infdtration of progenitors that differentiate into myelinating oligodendrocytes resulting in not only axon regrowth, but also myelination of these axons [36,41].…”
Section: Introductionmentioning
confidence: 99%
“…13 Delivery of mouse E14 spinal progenitors, loaded onto multichannel PLGA bridges providing a guidance architecture, showed marked improvement of axonal and functional regeneration in a mouse model of thoracic SCI. 196 However, another study found that collagen microfibers combined with neural progenitor cells from an alternative source failed to form a bridge across the injury site, or recovery of the motor function in a mouse SCI model. 39 It has been proposed that the combination of human MSCs and biomimetic hydrogels could modulate the immune cell microenvironment in SCI, leading to increased proregenerative M2 macrophage population.…”
Section: Reproduced Withmentioning
confidence: 99%
“…Smaller myelin debris was removed via density gradient centrifugation (63). In brief, a gradient was prepared such that a 35% (v/v) 1:1 4-morpholinepropanesulfonic acid (MOPS):Opti-prep (Sigma) solution in HBSS was layered on top of a 20% (v/v) 1:1 MOPS:Opti-prep solution in HBSS.…”
Section: Primary Preganglionic Sympathetic Neuron Isolationmentioning
confidence: 99%